نشاط الحزب الشيوعي العراقي في العام 1969 في ضوء الوثائق السرية العراقية - المنصراوي أحمد مريح; عبد عبد الله كاظم (lark, 2019)
Abstract Iraqi Communist Party, filled by government authorities in the third republican era for many years and were filled, and security circles reports minutes elaborate on the movements and activities of the communist elements and their influence in their bases mass, they showed those reports as well, the attention span of the ruling authority in scaling their activity and try to control them. The research activity of the Iraqi Communist Party during the 1969 to the importance of this year as it was a few months after the coup of July 17 to 30 in 1968, and the pursuit of the new leadership to control the movements of their enemies. Adopted in the writing of research on the Directorate of Military Intelligence reports and other important documents as well as the press, literature and publications of the Iraqi Communist Party and the sources of that period.